Aggregation-induced emission enhancement in charge-transporting derivatives of carbazole and tetra(tri)phenylethylene. (May 2017) - Tomkeviciene, A.; Sutaite, J.; Volyniuk, D.; Kostiv, N.; Simkus, G.; Mimaite, V.; Grazulevicius, J.V.
Abstract: New tri- or tetraphenylethylene-substituted phenylcarbazole derivatives exhibiting aggregation-induced emission were synthesized by the synthetic route including Pd-catalyzed Suzuki or Buchwald-Hartwig coupling and Heck reactions. The results of evaluation of the thermal, optical, electrochemical, photophysical, and charge-transporting properties of the synthesized derivatives are presented. The compounds possess high thermal stabilities with 5% weight loss temperatures exceeding 350 °C. Some of the synthesized compounds form glasses with glass transition temperature ranging from 77 to 114 °C. Their maximum fluorescence intensity wavelengths are in the range of 472–498 nm. The highest photoluminescence quantum yield of 43.9% was observed for the solid sample of 2-(4-(4-(1, 2, 2-triphenylvinyl)phenylethenyl)phenyl)-9-ethylcarbazole. The electron photoemission spectra of the films of the synthesized compounds revealed ionization potentials of 5.49–5.74 eV. Hole drift mobilities in the layers of 9-phenylcarbazole para- substituted with tri- or tetraphenylethylene moities reached 10 −3 cm 2 V −1 s −1 at moderate electric fields, as established by the time-of-flight technique. Graphical abstract: Highlights: New tri-/tetraphenylethylene-substituted carbazole derivatives exhibiting aggregation-induced emission (AIE) are designed and synthesized. Tetraphenylethylene moieties containing compounds with strongly enhanced emission in the aggregated state. The photoluminescence quantum efficiencies of the solid films ranging from 6 to 44%. The efficient charge carrier mobility (10 −3 cm 2 /V s) is observed in the synthesized materials.